2019
DOI: 10.1111/jiec.12853
|View full text |Cite
|
Sign up to set email alerts
|

The weight of islands: Leveraging Grenada's material stocks to adapt to climate change

Abstract: The building stock consumes large amounts of resources for maintenance and expansion which is only exacerbated by disaster events where large-scale reconstruction must occur quickly. Recent research has shown the potential for application of material stock (MS) accounts for informing disaster risk planning. In this research, we present a methodological approach to analyze the vulnerability of the material stock in buildings to extreme weather events and sea-level rise (SLR) due to climate change. The main isla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 29 publications
0
31
0
Order By: Relevance
“… 20 This novel method can also provide an improved high-resolution mapping to investigate urbanization, urban form, and infrastructure developments and inform infrastructure vulnerability studies. 36 …”
Section: Discussionmentioning
confidence: 99%
“… 20 This novel method can also provide an improved high-resolution mapping to investigate urbanization, urban form, and infrastructure developments and inform infrastructure vulnerability studies. 36 …”
Section: Discussionmentioning
confidence: 99%
“…However, these publications do not include studies on the circulation of material flows in shorter time scales. Only three research works have been identified as studying the relationship between a disaster and the development of metabolism: Symmes et al [36] study the consequences of a natural disaster (a cyclone and a rise in sea level) on building materials present on the Island of Grenada; Quinn [37] analyzes the impact of post-Katrina reconstruction on the New Orleans' metabolism; and Wildenberg and Singh [38] study the consequences of the 2005 tsunami and reconstruction on the socio-ecological system of the island of Kamorta, in the Nicobar archipelago. However, these works do not specifically concern disaster waste management.…”
Section: Specific Methodological Frameworkmentioning
confidence: 99%
“…It is also relevant to compare these indicators with those of the small islands that have already been studied [3,7,8,20]. The DMC in Iceland and in Trinidad are around 23 and 17 tons/capita/year, which is quite similar to New Caledonia (29.3 tons/capita/year).…”
Section: Spatialization Of Nexus: the Materials Footprint Of Islandsmentioning
confidence: 99%
“…These indicators are often combined with economic indicators to reveal the efficiency of productive systems and consumption patterns. Pioneer work has been carried out on the islands of Iceland, Trinidad, Grenada, or Samothraki in Greece [3][4][5][6][7] that has enabled, in very different contexts, us to understand the metabolic profiles of these islands and to describe the perspectives for local sustainability. Comparing resource consumption and the evolution of the gross domestic product (GDP) over a long period of time is also an expected objective of this research field, such as in the work of Martinico-Perez et al [8], who conducted a study of the socio-economic metabolism of the Philippine archipelago, in order to understand the evolution of island environmental pressures.…”
Section: Research On the Metabolism Of Islands: What Resilience And Smentioning
confidence: 99%